Biocontrol of Phenacoccus solenopsis Tinsley using entomopathogenic fungi and bacteria - El Aalaoui, Mohamed; Rammali, Said; Kamal, Fatima Zahra; Lefter, Radu; Calin, Gabriela; Burlui, Vasile; Ciobică, Alin; Petroaie, Antoneta Dacia; Novac, Otilia; Novac, Bogdan; Sbaghi, Mohamed (Frontiers in Sustainable Food Systems, 2024)
Introduction Phenacoccus solenopsis Tinsley, poses a significant threat to a range of crops worldwide. This study aimed to evaluate the efficacy of entomopathogenic fungi (Alternaria murispora and Alternaria destruens) and bacteria (Streptomyces bellus-E23-2) against adult females of P. solenopsis under laboratory (26 ± 2°C) and greenhouse conditions. Methods Laboratory trials tested A. murispora, A. destruens (104–1010 conidia mL−1), and S. bellus E23-2 (104–1010 cfu mL−1), alone and in combination, recording mortality rates and LC50 values. Greenhouse trials tested the best lab treatments on infested potato plants, monitoring pest density and plant quality. Results and discussion In laboratory trials, A. murispora at 1010 conidia mL−1 was the most effective, achieved 79.7% mortality (LC50 = 1.338 × 108 conidia mL−1 after 14 days). Combination treatments significantly enhanced efficacy, with A. murispora + S. bellus E23-2 (1010 conidia mL−1 + 1010 cfu mL−1) reaching 85.3% mortality. In greenhouse trials, the combination treatments notably reduced P. solenopsis densities and increased the number of infected mealybugs, with A. murispora + S. bellus E23-2 being the most effective. These treatments did not harm plant quality, unlike imidacloprid, which reduced visual quality despite its high efficacy. Alternaria murispora and S. bellus E23-2 effectively control P. solenopsis, providing a sustainable, plant-safe alternative to chemical insecticides.